A Study of the Perceptual Identification of the English Diphthongs by the Advanced Iraqi Student Teachers: Problems and Possible Solutions - Haifa Adnan Salman Al-Kan'aan (PROSPECTIVE RESEARCHES, 2023)
The perceptual identification of sounds is one of the most important areas in foreign-language learning. It often sets a precedent for sound discrimination, which should be practiced thoroughly in the earlier stages of learning English as a foreign language (EFL). Nevertheless, teaching experience has shown that misidentifying the sounds perceptually can be predicted in the performance of the Iraqi student teachers (AIST) majoring in English. This is mostly applied to the identification of vowels, in general, and that of diphthongs, in particular. The purpose of this paper is to find whether or not the AIST have some difficulties identifying the English diphthongs perceptually mostly because of the vowel system operating in their L1 which prevents them have an accent-free L2 and the lack of the appropriate exposure to a natively spoken L2, with the teacher as the only available model. The paper comes up with some possible solutions that can easily be adopted by the teachers of English in both earlier and advanced stages. The database for this study consists of the subjects' responses to the oral stimuli provided by the researcher, and the samples are taken from 12 students of the 5th year/ Dept. of English of the Teacher Training Institute/ Nineveh.